2009
DOI: 10.5194/acpd-9-18201-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wildfire smoke in the Siberian Arctic in summer: source characterization and plume evolution from airborne measurements

Abstract: Abstract. We present airborne measurements of carbon dioxide (CO2), carbon monoxide (CO), ozone (O3), equivalent black carbon (EBC) and ultra fine particles over North-Eastern Siberia in July 2008 performed during the YAK-AEROSIB/POLARCAT experiment. During a "golden day" (11 July 2008) a number of biomass burning plumes were encountered with CO concentration enhancements of up to 500 ppb relative to a background of 90 ppb. Number concentrations of aerosols in the size range 3.5–200 nm peaked at 4000 cm−3 and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…Information on agricultural fires north of 60°N, a minor emission source, is extremely scarce. While fires lead to increases in PM concentrations in the Arctic (Warneke et al, ; Yttri et al, ), such events tend to result from fires occurring at lower latitudes in Eurasia, particularly in Eastern Europe and Siberia, with subsequent transport of pollutants northward (Paris et al, ; Stohl et al, ). Regarding agricultural fires, Russia is the largest contributor with about 35% of global agricultural fires.…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…Information on agricultural fires north of 60°N, a minor emission source, is extremely scarce. While fires lead to increases in PM concentrations in the Arctic (Warneke et al, ; Yttri et al, ), such events tend to result from fires occurring at lower latitudes in Eurasia, particularly in Eastern Europe and Siberia, with subsequent transport of pollutants northward (Paris et al, ; Stohl et al, ). Regarding agricultural fires, Russia is the largest contributor with about 35% of global agricultural fires.…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…High extinction values are also observed in regions affected by biomass burning (e.g., Cummings, Yakutsk, and Kazakhstan), especially in spring and summer. According to Paris et al [2009] and Warneke et al [2009], intense fires took place in the Yakutsk and Kazakhstan regions during spring and summer 2008. These authors observed plumes between the surface and up to 6.5 km, which is consistent with our time series of the same regions, as also reported by Amiridis et al [2010].…”
Section: Aerosol Seasonal Variations In the Middle And High Latitudesmentioning
confidence: 99%
“…In remote area such as Yakutsk and Alaska, high CO mixing ratios are found in spring and summer for the former and in spring only for the latter. These high CO concentrations in Southeast Siberia and Alaska are very likely due to biomass burning emissions in Siberia [ Warneke et al , 2009; Paris et al , 2009]. High CO mixing ratios are also found in spring over East Asia and west Pacific in particular, but also, in lesser extent, everywhere in the middle and high latitudes.…”
Section: Aerosol Seasonal Variations In the Middle And High Latitudesmentioning
confidence: 99%
“…Under a doubled CO 2 scenario, General Circulation Models project a 4°–6°C rise in summer temperatures with a commensurate decrease in soil moisture for much of Canada and Russia thereby increasing fire danger by 50% and lengthening the fire season by 30 days [ Goode et al , 2000]. More frequent and severe fires will have a significant impact on the age class structure of vegetation, the carbon budget, air quality, and climate of the boreal/Arctic zone in particular [ Kasischke and Bruhwiler , 2002; Soja et al , 2004; Kasischke et al , 2005; Paris et al , 2009] and the globe in general.…”
Section: Introductionmentioning
confidence: 99%